GSTA1/CTNNB1 axis facilitates sorafenib resistance via suppressing ferroptosis in hepatocellular carcinoma - Shiwen Ma; Fei Xie; Xiaohu Wen; Yao Mawulikplimi Adzavon; Ruping Zhao; Jinyi Zhao; Han Li; Yanqi Li; Jingtao Liu; Chen Liu; Yang Yi; Pengxiang Zhao; et al. (Elsevier, 2024)
The emergence of sorafenib resistance has become a predominant impediment and formidable dilemma in the therapeutic approach for hepatocellular carcinoma (HCC). Although the approval of next-generation drugs as alternatives to sorafenib is a significant development, the concurrent use of inhibitors that target additional key molecular pathways remains an effective strategy to mitigate the acquisition of resistance. Here, we identified Glutathione S-Transferase Alpha 1 (GSTA1) as a critical modulator of sorafenib resistance (SR) in hepatocellular carcinoma (HCC) based on our findings from experiments conducted on recurrent liver cancer tissues, xenograft mouse models, organoids, and sorafenib-resistant cells. Elevated GSTA1 levels are strongly associated with adverse clinical prognoses. The knockout of GSTA1 reinstates sorafenib sensitivity, whereas its overexpression attenuates drug efficacy. Mechanistically, GSTA1 enhances the accumulation of lipid peroxides and suppresses ferroptosis by exerting its peroxidase function to regulate the SR. Notably, the upregulation of GSTA1 expression is mediated by the transcription factor CTNNB1 (β-catenin), resulting in the formation of a cytoplasmic complex between GSTA1 and CTNNB1. This complex facilitates the nuclear translocation of CTNNB1, establishing a positive feedback loop. The combined use of GSTA1 and CTNNB1 inhibitors demonstrated synergistic anti-tumour effects through the induction of ferroptosis both in vitro and in vivo. Our findings reveal a novel regulatory role of the GSTA1/CTNNB1 axis in ferroptosis, suggesting that targeting GSTA1 and CTNNB1 could be a promising strategy to circumvent sorafenib resistance in HCC.